(untitled) (Archives of Criminology, 2024)
The article addresses the factors influencing the effectiveness of the rehabilitation process for youth in Polish juvenile detention centers. A significant predictor of this effectiveness is considered to be the level of hope for achieving success in life. Here, hope is understood as one of the important social competencies. Therefore, based on the diagnostic survey method, from October to November 2021, a study was conducted to determine the level of hope characterizing the mentioned youth, using the Hope for Success Questionnaire by Charles R. Snyder, adapted to Polish by Mariola Łaguna, Jerzy Trzebiński, and Mariusz Zięba. The questionnaire was distributed by mail to all juvenile detention centers in Poland. Out of the returned questionnaires, 278 were qualified for further analysis. The results indicate a high level of optimism among the youth regarding their competencies to cope with life’s difficulties, and consequently, a high level of hope for achieving success. These results also form the basis for formulating methodological recommendations.